Analisis laporan keberlanjutan perusahaan di sub sektor barang baku logam dan mineral lainnya tahun 2019-2020 - C Susi Maryanti; Nurah Haerani; Rizky Meydina; Agus Munandar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research is to study and compare the level of completeness of the disclosure of the company's Sustainability Report in the Metal and Other Mineral Raw Goods Sub-Sector. The type of research used is qualitative research with descriptive analysis method of primary data on 4 company Sustainability Reports included in the sub-sector of raw metals and other minerals, namely the Sustainability Report of PT Aneka Tambang Tbk., PT Bumi Resources Mineral Tbk., PT Timah Tbk., PT Vale Indonesia Tbk., 2019 and 2020. In general, general disclosure, economic topics, environmental topics and social topics increased in 2020. This shows that the level of concern of the four companies to the community and stakeholders has increased. The total GRI Standards for general and topicspecific disclosures are 145 disclosures. Of this total, PT Aneka Tambang Tbk. made 74 disclosures or 51.03% in 2019 and 86 or 49.31% in 2020. PT Bumi Resources Mineral Tbk. made 66 disclosures or 45.53% in 2019 and 78 disclosures in 2020 or 53.79%. PT Timah Tbk. made 81 disclosures or 55.86% in 2019 and in 2020 as many as 75 disclosures or 51.72%. PT Vale Indonesia Tbk. made 69 disclosures or 47.59% in 2019 and 96 disclosures or 66.21% in 2020.